2017
DOI: 10.1038/mp.2017.245
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic landscape of the local translation at activated synapses

Abstract: The mammalian target of rapamycin (mTOR) signaling pathway is the central regulator of cap-dependent translation at the synapse. Disturbances in mTOR pathway have been associated with several neurological diseases, such as autism and epilepsy. RNA-binding protein FMRP, a negative regulator of translation initiation, is one of the key components of the local translation system. Activation and inactivation of FMRP occurs via phosphorylation by S6 kinase and dephosphorylation by PP2A phosphatase, respectively. S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…Previously, we conducted in silico experiments and showed that increased activity of the mTOR pathway might result in generating oscillatory (cyclic and quasi-cyclic), chaotic, and even hyperchaotic dynamics of FMRP-dependent postsynaptic protein synthesis. Our results suggested that ASD associated with mTOR pathway hyperactivation might be due to impaired proteome stability associated with complex dynamic regimes of protein synthesis in response to stimulation of mGluR receptors of excitatory synapses [28]. It is highly possible that any mutation in postsynaptic mTOR-or FMRP-targets additionally perturbs proteostasis and worsens autistic phenotype under the condition of mTOR pathway hyperactivation.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we conducted in silico experiments and showed that increased activity of the mTOR pathway might result in generating oscillatory (cyclic and quasi-cyclic), chaotic, and even hyperchaotic dynamics of FMRP-dependent postsynaptic protein synthesis. Our results suggested that ASD associated with mTOR pathway hyperactivation might be due to impaired proteome stability associated with complex dynamic regimes of protein synthesis in response to stimulation of mGluR receptors of excitatory synapses [28]. It is highly possible that any mutation in postsynaptic mTOR-or FMRP-targets additionally perturbs proteostasis and worsens autistic phenotype under the condition of mTOR pathway hyperactivation.…”
Section: Discussionmentioning
confidence: 82%
“…Disease and functional enrichment analysis indicate that the top 20 largest miRNA–target regulatory modules are significantly enriched in 397 GO terms, 3 KEGG pathways, 12 Reactome pathways, and 69 DisGeNET terms. Specifically, several biological processes, pathways, and diseases, including anxiety disorder (umls: C0003469) ( White et al, 2009 ), Alternative mRNA splicing (GO: 0000380) ( Quesnel-Vallieres et al, 2019 ), circadian rhythm (GO: 0007623) ( Hu et al, 2017 ), and mTOR signaling pathway (R-HSA-165159) ( Khlebodarova et al, 2018 ) are closely related to ASD ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, local translation of Camk2 mRNA is controlled by a balance between RISC, a component of RNA interference, and proteasome, which works for degradation of RISC (Ashraf et al, 2006). These accurate regulations of local translation probably increase signal and noise ratio of synapses to establish circuits for cognitive functions, on the other hand, disruption of the system may link to cognitive impairments and neuropsychiatric disorders (Khlebodarova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%